Selection of Conditions for the Synthesis of Methacrylate Monomers Based on Adamantane - Novikov, Alexander S.; Malkov, Georgiy V.; Akkuratov, Alexander V. (Synlett, 2024)
Adamantane-based methacrylates are important monomers for the design of polymers used for the development of chemically amplified photoresists. Herein, we present the selection of reaction conditions for obtaining of 2-ethyladamantan-2-yl methacrylate, 2-methyladamantan-2-yl methacrylate, adamantan-1-yl methacrylate, and 3-hydroxyadamantan-1-yl methacrylate from adamantane derivatives and methacryloyl chloride. It is shown that the combination of pyridine as a solvent and base with 1,4-diazabicyclo[2.2.2]octane (DABCO) as a base allows reproducible preparation of the desired products with good yields. The results obtained provide valuable information for upscaling the synthesis of important products for the microelectronics industry.
Keywords: DUV photolithography; photoresist monomers; adamantyl methacrylates; reaction conditions; DABCO; acylation